Iridoid glycoside permethylation enhances chromatographic separation and chemical ionization. (14th August 2016) - Elmasri, Wael A.; Yang, Tianjiao; Hegazy, Mohamed‐Elamir F.; Mechref, Yehia; Paré, Paul W.
Abstract : Rationale: While natural products isolated from medicinal plants can serve as a rich source of biologically active metabolites, mixtures of structurally related compounds of a polar nature are often difficult to chemically resolve by traditional separation techniques. Chemical derivatization to reduce metabolite polarity combined with liquid chromatography (LC) is the strategy presented here to resolve a mixture of structurally related natural product glycosides solvent extracted from the medicinal herb Teucrium polium for mass spectrometric characterization. Methods: The partially purified plant extract was subjected to chemical derivatization and electrospray ionization mass spectrometry (ESI‐MS) fragmentation pattern analysis allowed for structural characterization of iridoid and secoiridoid glycosides. Selected ions were subjected to tandem mass spectrometric (MS/MS) analysis with a relatively higher‐energy collision dissociation to assist in structural elucidation. Results: Permethylation replaced all protons from free hydroxyl and amino groups with methyls and resulted in increases in both hydrophobicity, for facilitated chromatographic separation, and proton affinity, for enhanced chemical ionization. Protonated and/or sodiated adducts were observed for the six compounds detected in positive‐ion mode ESI‐MS with a mass accuracy of less than 2 ppm. Conclusions: Permethylation combined with LC/MS analysis is shown here to be an effective chemical practice for separating and characterizing iridoid glucosinolates and is expected to be well suited for the chemical characterization of other polar natural‐product mixtures of closely related compounds. Copyright © 2016 John Wiley & Sons, Ltd.